Самый глупый ангел - Мур Кристофер (Интеллектуальный бестселлер, 2011)
Экземпляры: СФ-20 (20120827) / Инвентарный номер: 41024z20 / Цена: 232.27 / Сис.шифр: 84(7Сое) / Авт.знак: М 91 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)